(1/sinA-sinA)(1/cosA-cosA)=1/tanAcotA
Answers
Answered by
4
Hey friend,
Here's your answer.
cosecA-sinA)(secA-cosA)
=(1/sinA – sinA )(1/cosA – cosA)
=[(1- sin2A)/sinA][(1-cos2A)/cosA]
=[(cos2A)/sinA][(sin2A)/cosA]
=sinA*cosA
\frac{sinA cosA}{sin^2A + cos^2A}
= \frac{1}{sin^2A/sinA cosA + cos^2A/sinA cosA }
=\frac{1}{tanA + cotA }
=rhs
I hope this helps you
Here's your answer.
cosecA-sinA)(secA-cosA)
=(1/sinA – sinA )(1/cosA – cosA)
=[(1- sin2A)/sinA][(1-cos2A)/cosA]
=[(cos2A)/sinA][(sin2A)/cosA]
=sinA*cosA
\frac{sinA cosA}{sin^2A + cos^2A}
= \frac{1}{sin^2A/sinA cosA + cos^2A/sinA cosA }
=\frac{1}{tanA + cotA }
=rhs
I hope this helps you
Answered by
9
Heyy Buddy ❤
Here's your Answer..
(1/sinA-sinA)(1/cosA-cosA)=1/tanAcotA
L.H.S.
=>[ (1 - sin^2A)/sinA ] [ (1 - cos^2A)/cosA]
=> (Cos^2A/ SinA ) ( Sin^2A/ CosA)
=> (SinA × CosA) /1
we know that, Sin^2A + Cos^2A = 1
So,
=> (SinA × CosA) /( sin^2A + Cos^2A)
=> Dividing Denominator and Numerator by SinA × CosA
=>[(siA× cosA)/ (sinA × CosA)]/ [(sin^2A / sinA × CosA) + Cos^2A/ sinA × CosA]
=> 1/ [(sin^2A / sinA × CosA) + Cos^2A/ sinA × CosA]
=> 1 / [(sinA/CosA) + (CosA/ sinA)]
=> 1 / [ tan A + CotA]
=> 1/ Tan A + cotA.
✔✔✔
Here's your Answer..
(1/sinA-sinA)(1/cosA-cosA)=1/tanAcotA
L.H.S.
=>[ (1 - sin^2A)/sinA ] [ (1 - cos^2A)/cosA]
=> (Cos^2A/ SinA ) ( Sin^2A/ CosA)
=> (SinA × CosA) /1
we know that, Sin^2A + Cos^2A = 1
So,
=> (SinA × CosA) /( sin^2A + Cos^2A)
=> Dividing Denominator and Numerator by SinA × CosA
=>[(siA× cosA)/ (sinA × CosA)]/ [(sin^2A / sinA × CosA) + Cos^2A/ sinA × CosA]
=> 1/ [(sin^2A / sinA × CosA) + Cos^2A/ sinA × CosA]
=> 1 / [(sinA/CosA) + (CosA/ sinA)]
=> 1 / [ tan A + CotA]
=> 1/ Tan A + cotA.
✔✔✔
Similar questions